Recent Changes in Storm Track over the Southeast Europe: A Mechanism for Changes in Extreme Cyclone Variability - Mihaela Caian; Florinela Georgescu; Mirela Pietrisi; Oana Catrina (Atmosphere, 2021)
Recent changes in cyclone tracks crossing Southeast Europe are investigated for the last few decades (1980–1999 compared with 2000–2019) using a developed objective method. The response in number, severity, and persistence of the tracks are analyzed based on the source of origin (the Mediterranean Sea sub-domains) and the target area (Romania-centered domain). In winter, extreme cyclones became more frequent in the south and were also more persistent in the northeast of Romania. In summer, these became more intense and frequent, mainly over the south and southeast of Romania, where they also showed a significant increase in persistence. The regional extreme changes are related to polar jet displacements and further enhanced by the coupling of the sub-tropical jet in the Euro-Atlantic area, such as southwestwards shift in winter jets and a split-type configuration that shifts northeastwards and southeastwards in the summer. These provide a mechanism for regional variability of extreme cyclones through two paths, respectively, by shifting the origins of the tracks and by shifting the interaction between the anomaly jet streaks and the climatological storm tracks. Large-scale drivers of these changes are analyzed in relation to the main modes of atmospheric variability. The tracks number over the target domain is mainly driven during the cold season through a combined action of AO and Polar–European modes, and in summer by the AMO and East-Asian modes. These links and the circulation mode’s recent variability are consistent with changes found in the jet and storm tracks.